DEVELOPING TAHFIZ CURRICULUM IN MAN 2 KULON PROGO DURING THE PANDEMIC COVID-19 - Rina Sarifah; Asnawi Wijayanto; Hendro Widodo (The University of Kuningan, 2021)
This research started from curiosity about the role in developing the Tahfiz MAN 2 Kulon Progo curriculum during the Covid-19 pandemic. This study aims to determine the extent of the development Tahfiz MAN 2 Kulon Progo curriculum during the Covid-19 pandemic. The method in this study is qualitative research, the subject of the research is several PAI teachers who also become tahfiz supervisors with data collection techniques using interviews and documentation. The results of this study are 1) the basis for curriculum development based on the mandatory tahfiz from the Ministry of Religion of the Republic of Indonesia, namely creating high-intellectual Qur'an memorizers, 2) the basis for curriculum development based on the number of students who have embryos memorizing the Qur'an, 3) The basic curriculum development aims to explore the potential of students who have a good reading but do not yet have memorized the Qur'an, 4) the basis for curriculum development is to support religious understanding competence, and 5) the basis for curriculum development is to preserve religious scientific traditions. The conclusion of curriculum development is to create memorizers of the Qur'an, assist students in memorizing the Qur'an and assist students in making it easier to achieve the desired competencies.